INTERFERENSI BAHASA INDONESIA DALAM BAHASA BAKUMPAI DALAM CERITA “MANG RAJA HAJI DENGAN UJU PUTRINYA” INDONESIAN INTERFERENCE IN BAKUMPAI LANGUAGE IN THE BAKUMPAI FOLKLORE "MANG RAJA HAJI DENGAN KEUJU PUTRINYA" - SITI JAMZAROH (Multilingual, 2020)
Abstract             This study aims 1) to describe the morphological interference events, and 2) to describe the lexical interference events; Indonesian in the Bakumpai language in a story entitled Mang Raja Haji with his daughter's Keuju. The method used in this research is data provision, data processing, and data analysis. Provision of data using the technique of engaging free listening proficiently and technique of note taking. Data processing is done by using the triangulation technique with the help of dictionaries and native speakers of Bakumpai language informants. Data analysis was carried out by classifying data based on word categories and types of interference found. The findings are 1) morphological interference occurs in verbal words and phrases, 2) lexical interference occurs in types of words or phrases: verbal, adjective, adverbial, conjunction, and noun.            Key Word, interferensi, trianggulasi, frasa AbstrakPenelitian ini bertujuan  1) mendskripsikan peristiwa interferensi morfologi, dan 2) mendeskripsikan peristiwa interferensi leksikal; bahasa Indonesia dalam bahasa Bakumpai dalam cerita yang berjudul Mang Raja Haji dengan Keuju Putrinya. Metode yang digunakan dalam penelitian ini adalah  penyediaan data, pengolahan data, dan penganalisasisan data. Penyediaan data dengan menggunakan teknik simak bebas libat cakap dan teknik  catat, Pengolahan data dilakukan dengan mengunakan teknik trianggulasi dengan bantuan kamus dan informan penutur asli Bahasa Bakumpai. Penganalisisan data dilakukan dengan mengklasifikasikan data berdasarkan kategori kata, dan jenis interferensi yang ditemukan. Hasil temuannya adalah 1) interenferesi morfologi tejadi pada kata dan frasa verbal, 2) interferensi leksikal terjadi pada jenis kata atau frase:  verbal, adjektiva, adverbial, konjungsi, dan nomina,            Key Word, interferensi, trianggulasi, frasa